Coexisting primary tumors from esophageal cancer and myelodysplastic syndromes: A case report - Imamura, Hiroki; Tamura, Shigeyuki; Hattori, Hideki; Kidogami, Shinya; Mokutani, Yukako; Kishimoto, Tomoya; Hashimoto, Yasuji; Hirose, Hajime; Yoshioka, Shinichi; Kuwayama, Maki; Endo, Shunji; Sasaki, Yo (Clinical case reports, 2021)
This is the first report of the double primary cancer of esophageal cancer (EC) and myelodysplastic syndromes (MDS) treated without esophagectomy. Previously reported cases of the double cancer mostly describe secondary MDS arising after treatment for EC. The double primary cancer was manageable with close follow‐ups for possible recurrence. This is the first report of the double primary cancer of esophageal cancer (EC) and myelodysplastic syndromes (MDS) treated without esophagectomy. Previously reported cases of the double cancer mostly describe secondary MDS arising after treatment for EC. The double primary cancer was manageable with close follow‐ups for possible recurrence.